Relation between the Algebra of Currents and their Definition in Chiral Gauge Theories - Fosco, C.; Trinchero, R. C. (Comisión Nacional de Energía Atómica; Argentina)
Fil: Fosco, C. Comisión Nacional de Energía Atómica; Argentina